(untitled) (Theatrum historiae, 2007)
The article focuses on the personality of Matouš Radouš, a painter, (†1631), of the town Chrudim, and with his outstanding and partly well preserved work – the epitaphs of prominent Chrudim burghers. Extraordinary position of Matouš Radouš lies in the fact that we only know a few painters of Czech origin in the period of Renaissance. Thanks to the sufficient archive sources, we know a lot of his life and together with his paintings, still preserved in Chrudim churches (in Church of the Assumption of the Virgin Mary and St. Michael) they were intended for, we can imagine how the local Late Renaissance workshop functioned. The research into the life and work of the “regional” Renaissance painter Matouš Radouš has several aspects. One of them is formal characteristic of the epitaphs representing a typical Central-European works of art adopting the Mannerist art influence mediated though the court of Rudolph II in Prague. We can observe how compositions of Matouš Radouš’s epitaphs reflect the figural canon and the patterns of international Mannerism, transmitted especially by graphics. Nevertheless, the character of Radouš represents a typical local “shift” from the exclusive court art and the art of a rather low formal quality. On the other hand, formal aspect of Radouš’s artistic production should not be the only one to appreciate his works of art. The unique group of Chrudim epitaphs (produced between 1580 and 1630) by Radouš and his collaborators represent a source of this kind. On the one hand, the epitaphs reflect social position of civic elite in Early Modern Chrudim and special culture of creating personal and social remembrance. On the other hand, the epitaphs witnessed the interesting confessional situation in the town. In some cases, a very original iconography of these epitaphs (e.g. the motif of Allegoric Crucifixion) proves that the commissioners of this monument were non-Catholics. The change in iconography after the White Mountain Battle, using the new Catholic motifs (esp. of the Virgin Mary) shows that the confessional situation in the town was also changed in favour of Catholicism. Last but not least, the unique epitaphs by Radouš not only represent the “works of art”, but they also stand for special records of a great historical-anthropological value.